PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK BERBANTUAN MEDIA POP UP BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 3 RANTEPAO - Sarina Daud; Roberto S. Situru; Irene Hendrika Ramopoly (LPSDI Bina Patria, 2025)
The aim of this study is to improve the early reading ability of second-grade students at SDN 3 Rantepao through the application of the structural analytic synthetic method assisted by Pop Up Book media. The approach used in this research is qualitative to describe the activities of teachers and students in the learning process, and the type of research used is Classroom Action Research (CAR). The CAR model to be used in this study is the Kemmis and McTaggart model, which is a cyclical model conducted repeatedly and continuously. Each cycle consists of the stages of action planning, action implementation, observation, reflection, and planning for the next cycle. This research shows that the students' early reading ability increased. This can be seen from the increase in the completeness score of students' formative test results from 54.16% in the first cycle to 91.66% in the second cycle, indicating that the application of the structural analytic synthetic method assisted by Pop Up Book media can improve early reading ability.